The Evolution and Communicational Aspects of Mediation (Academic Journal of Internal Affairs, 2020)
Since mediation, as a form of alternative dispute resolution, has become part of the canonized legal system, it has come to life and has made its own path of development from the 1950s to the present. In this paper, the process and the stages of it are discussed from communicational point of view through the terminology of the PTC. The sections also represent the types of mediation. Relationships and interactions between the types are also the subject of this study, as well as the scopes for certain types. The participatory theory of communication (PTC) allows us to review the development of mediation in the 20th and 21st centuries, from a facilitative mediation to a transformative mediation, according to a unified, transparent framework.
Keywords: mediation; problem solving consensus building; participatory theory of communication (PTC); system theory